Fostering Diversity and Inclusion in the National Heart, Lung, and Blood Institute’s Small Business Program - Padmore, Eric W. (Ethn Dis, 2019)
The National Heart, Lung, and Blood Institute has developed a strategic approach to fostering diversity and inclusion within its community of small business innovators. The approach is focused on three central goals: 1) Increase awareness of NHLBI’s support for small businesses among underrepresented groups through focused outreach; 2) Identify and eliminate barriers to entry into small business funding programs and entrepreneurial activities for minority and female applicants through specific, targeted training and support; and 3) Expand diversity and inclusivity within our networks by providing additional support for NHLBI-funded small businesses to hire members of underrepresented groups. Key partnerships with biomedical accelerators in underserved regions will be leveraged to maximize impact and achieve all three goals. This article describes the historical context and current state of policies in this arena; it also provides details about mechanisms and approaches used to achieve the goals.